International Environment as a Factor for Internationalisation of Polish Firms - Wach, Krzysztof (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2016)
While explaining the internationalisation processes of firms (especially SMEs), the general models of international entrepreneurship generally use the following three groups of variables: (i) the entrepreneur as a key element of the model, including its characteristics, cognition, perception and dynamic competences, (ii) environmental conditions (i.e. the business environment), including those inherent in the domestic market and in international markets, (iii) the entrepreneurial process of recognizing market opportunities, including the discovery of entrepreneurial opportunities, their evaluation and utilization. International conditions for the internationalization of firms or external conditions inherent in a foreign environment, are one of the three main variables of internationalization process of firms from the perspective of international entrepreneurship. The main objective of this article is to identify the key factors inherent to internationalization of firms in the international environment and the exploration of the impact of these factors on the internationalization process of Polish firms. The article presents the partial results of survey based on a sample of 355 firms operating in Poland. The questionnaire was completed in 2015 within OPUS 4 project carried out at the Faculty of Economics and International Relations of the Cracow University of Economics.